Study of different acute SIT protocols’ impact on 200m sprinters’ anaerobic performance - Liu, Ying; Liu, Qi; Gong, Zhigang; Yan, Junqian; Yan, Juntao (Frontiers in Physiology, 2025)
IntroductionSprint interval training (SIT), characterized by its “all-out” maximal-intensity efforts, elicits substantial energy output in a short duration, demonstrating superior anaerobic performance. This study compared the acute effects of different SIT protocols to identify the optimal training combination for enhancing anaerobic capacity in 200-m sprinters.MethodsTwelve male 200-m sprinters performed SIT sessions in a 2 (sprint duration: 20s, 30s) × 3 (load: 7.5%, 9%, 10% body mass (BM)) × 4 (repetitions) design with 4-min inter-set rest, assessed via anaerobic power, electromyography (EMG), and blood lactate measures.Results(1) Duration and load significantly affected peak power (PP), mean power (MP), and fatigue index (FI) (P < 0.05); (2) Sprint duration significantly influenced lower-limb integrated EMG (IEMG) and median frequency (MPF) (P < 0.05), with no notable interaction effects; (3) Both duration and load significantly modulated muscle activation (RMS%) in the rectus femoris, biceps femoris, and vastus lateralis (P < 0.05), but not in the gastrocnemius; (4) Duration significantly increased maximal blood lactate, accumulated lactate, and rating of perceived exertion (RPE) (P < 0.05), whereas load had no independent effect; (5) The interaction between duration and load exhibited highly significant effects on anaerobic performance (P < 0.01).ConclusionA high-intensity SIT protocol comprising 4 × 20s all-out sprints at 10%BM load with 4-min rest intervals optimally enhances 200-m sprinters’ anaerobic capacity through multidimensional physiological stimuli, providing an effective training strategy for performance optimization.